Development and Validation of Nomogram for Predicting Survival of Primary Liver Cancers Using Machine Learning - Chen, Rui; Hou, Beining; Qiu, Shaotian; Shao, Shuai; Yu, Zhenjun; Zhou, Feng; Guo, Beichen; Li, Yuhan; Zhang, Yingwei; Han, Tao (Frontiers in Oncology, 2022)
Background and Aims: Primary liver cancer (PLC) is a common malignancy with poor survival and requires long-term follow-up. Hence, nomograms need to be established to predict overall survival (OS) and cancer-specific survival (CSS) from different databases for patients with PLC. Methods: Data of PLC patients were downloaded from Surveillance, Epidemiology, and End Results (SEER) and the Cancer Genome Atlas (TCGA) databases. The Kaplan Meier method and log-rank test were used to compare differences in OS and CSS. Independent prognostic factors for patients with PLC were determined by univariate and multivariate Cox regression analyses. Two nomograms were developed based on the result of the multivariable analysis and evaluated by calibration curves and receiver operating characteristic curves. Results: OS and CSS nomograms were based on age, race, TNM stage, primary diagnosis, and pathologic stage. The area under the curve was 0.777, 0.769, and 0.772 for 1-, 3- and 5-year OS. The AUC was 0.739, 0.729 and 0.780 for 1-, 3- and 5-year CSS. The performance of the two new models was then evaluated using calibration curves. Conclusions: We systematically reviewed the prognosis of PLC and developed two nomograms. Both nomograms facilitate clinical application and may benefit clinical decision-making. Keywords: Primary liver cancer; SEER; TCGA; nomogram